Investimento estrangeiro direto no Brasil: economia política e regime jurídico - Begosso, Ricardo (2020)
Foreign Direct Investment (FDI) is usually characterized as the productive modality of foreign capital inflows into the country. Nevertheless, its financial and technological dimensions are inseparable. More than an accounting relationship that impacts the balance of payments and macroeconomic indicators, FDI needs to be studied as an economic relationship between the country and abroad. This work intends to shed light on the historical inadequacy of the FDI legal regime in Brazil. To this end, it starts with a study on the political economy of FDI in the first chapter, with the aim of investigating the reasons why production moves internationally, in particular from central countries to peripheral countries. Here special attention will be paid to the technological dimension of capital and its implications as a determinant of capital flows, without abstracting from the historical and geopolitical conditions that act to modulate these flows, accelerating or resisting their structural impulses. Then, an attempt is made to integrate into the theoretical panorama analyzed in the first chapter a historical reading of the formation of the FDI legal regime in Brazil. The technological aspect of FDI is more visibly linked to the financial aspect, revealing how the technological transfer conducted in the second half of the 20th century originated the classic problem of profit remittances. The second chapter characterizes an effort to understand this phase of Brazilian development, noting that the abandonment of the practice of bargaining with foreign capital, especially after 1964, resulted in an increase in dependence on FDI and in the frustration of subsequent attempts to affirm the national technological autonomy.